LOW SODIUM DIET: PROS AND CONS - O. M. Drapkina; R. N. Shepel' (Столичная издательская компания, 2015)
Currently, there is rather contradictory evidence on the effectiveness of a low sodium diet for the prevention of various diseases. At that, it is a generally accepted fact, that it is necessary to reduce salt intake in order to reduce high blood pressure. An internist should remember that the degree of blood pressure reduction is individual and not always depends on the level of salt intake. Moreover, the low-sodium diet helps to reduce the rate of telomere shortening, thereby slowing down the aging process.